The importance of being wise or could "Museum archaeology" help us be better professionals - Šola, Tomislav (Array, 2004)
Museums are burdened with inner incapacity to fight for their community. It is a long list of problems. The solution to them is equally long but the list of actions begins with understanding of heritage, its role in the society and its mechanisms of action.